Analisis Mix Design Batako Dengan Penambahan Limbah Kayu Pada Kuat Tekan Standar - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Tjokro Hadi (Teknis, 2014)
Waste sawn wood workshop practice POLINES is the waste generated from the waste due to the activity of the sawmill, this garbage is quite a lot and often cause problems in management, regular cope with burnt which eventually lead to air pollution, and pollution due to ash that can be carried by angin.Penelitian this aims to assess the sawn wood waste used as aggregate in the manufacture of cement bricks, useful things of this study is to provide a solution to the waste problem sawn wood, brick and creating products that are cheap so it can reduce the cost of construction perumahan.Hasil research suggests that sawn wood can be used as materials for cement bricks, cement bricks in terms of the severity of the aggregate of sawn timber belonging cukuo brick weighs about 1100 grams lighter which is equal to the brick or ceramic circulating in Semarang (Supardjo Research, 2002).Keywords: Waste wood workshop practice POLINES, Batako.